Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This edited book presents scientific results of the 17th IEEE/ACIS International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD 2016) which was held on May 30 - June 1, 2016 in Shanghai, China. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the numerous fields of computer science and to share their experiences and exchange new ideas and information in a meaningful way. Research results about all aspects (theory, applications and tools) of computer and information science, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them.
Dealing with Missing Values in Software Project Datasets: A Systematic Mapping Study -- Testing and Code Review Based Effort-Aware Bug Prediction Model -- Improving the Efficiency of Schedulability Tests for Fixed Priority Preemptive Systems -- A GPU Accelerated Finite Differences Method of the Bioheat Transfer Equation for Ultrasound Thermal Ablation -- Justifying the Transition from Trustworthiness to Resiliency via Generation of Safety Cases -- Selectand Test (ST) Algorithm for Medical Diagnostic Reasoning -- Opportunities ahead the Future Mobile Learning -- A Design of Context-Aware Framework for Conditional Preferences of Group of Users -- Design of Decentralized Inter-Cell Interference Coordination Scheme in LTE Downlink System -- Toward Flow-Based Ontology -- Mobile Component Integration Agent (MCIA) for Social Business Application -- Covariance Estimation for Vertically Partitioned Data in a Distributed Environment -- Detection of Dengue Epidemic in Dhaka, Bangladesh by a Neuro Fuzzy Approach -- MIMO Antenna Design for Future 5G Wireless Communication Systems.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence